Picturing Sabino : a photographic history of a southwestern canyon - Lazaroff, David Wentworth, 1948- (Southwest Center series., 2023)
"This history of Sabino Canyon shows like never before why this mountain canyon near Tucson, Arizona, is such a beloved place. With more than 200 images and engaging text, David Wentworth Lazaroff relays [and] relates 100 years of history, revealing how the canyon changed from a little-known oasis into an immensely popular recreation area on the edge of a modern metropolis"--